Analisis Perkembangan Sosial Emosional Anak Usia 5-6 Tahun di Kelompok B TK Al Hijrah Gorontalo - Mia Nur Ara; Dea Prananda; Ravika Latedu; Iyutri Ladiku (Prodi Sastra Jepang Universitas Ngudi Waluyo, 2025)
This study aims to analyze the social and emotional development of early childhood in Group B at Al Hijrah Kindergarten, Gorontalo. Social and emotional development is a fundamental aspect of a child's growth and development because it influences their ability to interact, regulate emotions, build social relationships, and adapt to their environment. This study used a descriptive qualitative approach with observation and interview techniques involving children and teachers as the primary data sources. The results showed that most children in Group B had well-developed social skills, such as the ability to cooperate, share, show empathy, and communicate with peers. However, some children still faced challenges in managing their emotions, including difficulty expressing feelings appropriately and controlling behavior when facing situations that trigger conflict. These findings emphasize the crucial role of teachers in providing consistent stimulation through responsive learning approaches, structured play activities, and a supportive learning environment. This study recommends strengthening social and emotional stimulation strategies through interactive activities, cooperative play, and effective communication to optimize and enhance children's holistic development.